STRATEGI BRANDING HALAL PT INDOFOOD DALAM EKSPANSI GLOBAL DI PASAR MUSLIM - Yahya, Wardah; Akbar Pangestu, Muhammad Gibran (Taksasila Edukasi Insani, 2024)
His research analyzes the halal branding strategy of PT Indofood CBP Sukses Makmur Tbk in supporting global expansion in the international Muslim market. The main focus of the research is on the use of product innovation, halal certification, and local culture-based promotion as strategies to increase competitiveness and loyalty of Muslim consumers. By integrating sharia principles and Islamic business practices, Indofood has successfully expanded its product range to more than 80 countries, including the Middle East, Africa, and Asia. The results show that globally recognized halal certification and product customization to local preferences are the main factors for the success of this strategy. However, challenges such as variations in halal regulations between countries and increasing global competition are still issues that need to be addressed. This study provides recommendations for other multinational companies in optimizing halal branding as a strategic tool to expand the international Muslim market. Keywords : Global expansion, Halal branding, Islamic business strategy, Muslim market, PT Indofood CBP